Pengembangan modul pembelajaran berbasis masalah pada materi pencemaran lingkungan untuk meningkatkan hasil belajar siswa - Sri Yustika Candri Pakaya; Lilan Dama; Marini Susanti Hamidun; Elya Nusantari; Dewi Wahyuni K. Baderan; Abubakar Sidik Katili (Postgraduate, University of Mataram, 2023)
This research was calssifed as a Research and Development (R&D) that aimed to detemine the validity, practicality, and effectivenes of developing problem-based learning module to improve students’ learning outcomes. The samples consisted of 20 students in class X of SMA Negeri 7 PrasetyaGorontalo. This research was conducted to create module tahtreffered to the ADDIE model (Analysisi, Design, Development, Impelemntation, and Evaluation), but it was only limited to the development stage, namely the limited trial develpment stage. The instruments used were interview, validation sheet, and student response questionnaire, implementation of learning (teacher activity), student activity, and pre-test dan post-test. Teh result of module validation analysis with here validators obtained an average score of 85% (very valid). Meanwhile, the result of practicality analysis was observable from the teacher activity which obtained an average score of 93.3% (very good), the student activity in the small group trial obtained an average score of 90% (very good), and the student responses obtained an average score 88% (very feasible). In the meantime, the result of effectiveness analysis were observable from the result of N-Gain analysis in small group trial which obtained an average score of 0.62% (fairly effective). To conclude, the development of problem-based module on enviromental pollution topic intending to improve the students’ learning outcomes had met the valid and practical criteria but has not been effetive due to it only reached a limited trial. However, the module was feasible to use in the learning process.